Population genomics analysis of yellowfin tuna Thunnus albacares off South Africa reveals need for a shifted management boundary - Mullins, Rachel Brenna (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2017)
Yellowfin tuna Thunnus albacares is a commercially and economically important fisheries species, which comprises the second largest component of South Africa's catch of tuna and tuna-like species. Catches of the species off South Africa are treated as two discrete stocks by the two tuna Regional Fisheries Management Organisations (tRFMOs) under whose jurisdictions they fall. Individuals caught off the Western Cape, west of the boundary between the tRFMOs at 20Â°E, are included in assessment and management of the Atlantic Ocean yellowfin tuna stock by the International Commission for the Conservation of Atlantic Tunas (ICCAT), and those caught east of this boundary are assessed and managed as part of the Indian Ocean stock by the Indian Ocean Tuna Commission (IOTC). The boundary between these stocks is based on the confluence of the two oceans in this region and does not incorporate the population structure of species. For sustainable exploitation of fisheries resources, it is important that the definition of management stocks reflects species' biological population structure; the fine-scale stock structure of yellowfin tuna off South Africa is therefore a research priority which this study aimed to address by means of population genomics analyses. Yellowfin tuna exhibit shallow genetic differentiation over wide geographic areas, and as such traditional population genetic approaches have limited power in resolving fishery significant population structure in the species. Herein, a population genomic approach was employed, specifically, genome-wide analysis of single nucleotide polymorphisms (SNPs) discovered using a next-generation DNA sequencing approach, to confer (i) increased statistical power to detect neutral structuring reflecting population connectivity patterns and (ii) signatures of local adaptation. The mitochondrial Control Region (mtDNA CR) was also sequenced to compare the resolving power of different approaches and to permit coalescent based analyses of the species evolutionary history in the region. Neutral SNP loci revealed significant structure within the dataset (Fst=0.0043; P<0.0001); partitioning of this differentiation within the dataset indicated significant differentiation between yellowfin tuna from the Western Cape and the Gulf of Guinea in the eastern Atlantic Ocean, with no significant differentiation between individuals from the Western Cape and Western Indian Ocean regions. This indicates two population units wherein there is a separation of the Gulf of Guinea from the remaining samples (Indian Ocean including Western Cape) that are largely derived from a single genetic population. This pattern was also supported by assignment tests. Positive outlier SNPs, exhibiting signatures of diversifying selection, suggest that individuals from these regions may be locally adapted, as well as demographically isolated. The mtDNA CR did not reveal any significant genetic structure among samples (Fst=0.0030; P=0.309), demonstrating the increased resolving power provided by population genomics approaches, but revealed signatures of historical demographic fluctuations associated with glacial cycles. Based on the findings of this study, it is suggested that yellowfin tuna caught off the Western Cape of South Africa are migrants from the Indian Ocean population, exhibiting significant genetic differentiation from the Atlantic Ocean Gulf of Guinea individuals, and should thus be included in the assessment and management of the Indian Ocean stock. It is therefore recommended that the boundary between the Atlantic and Indian Ocean yellowfin tuna stocks, under the mandates of ICCAT and the IOTC respectively, should be shifted to approximately 13.35Â°E to include all individuals caught in South African waters in the Indian Ocean stock.
Keywords: Yellowfin tuna fisheries -- South Africa -- Western Cape; Genomics; Tuna fisheries -- South Africa; Fishery management -- South Africa